A systematic review and meta-analysis of randomized controlled trials of cognitive behavior therapy for insomnia (CBT-I) in cancer survivors. (June 2016) - Johnson, Jillian A.; Rash, Joshua A.; Campbell, Tavis S.; Savard, Josée; Gehrman, Philip R.; Perlis, Michael; Carlson, Linda E.; Garland, Sheila N.
Summary: This review examined the efficacy of cognitive behavior therapy for insomnia (CBT-I) in people diagnosed with cancer. Studies were identified through November 2014 using multiple databases, clinical trial records, and bibliography searches. Inclusion was limited to randomized controlled trials of CBT-I conducted in individuals with a cancer diagnosis who had clinically relevant insomnia. The primary outcome variable was sleep efficiency (SE) as measured by sleep diary. Eight studies including data from 752 cancer survivors met inclusion criteria. CBT-I resulted in a 15.5% improvement in SE relative to control conditions (6.1%) from pre- to post-intervention, with a medium effect size (ES: d = 0.53). Overall, sleep latency was reduced by 22 min with an ES of d = 0.43, compared to a reduction of 8 min in the control conditions. Wake after sleep onset was reduced by 30 min with an ES of d = 0.41, compared to 13 min in the control conditions. Large effect sizes were observed for self-reported insomnia severity ( d = 0.77) for those patients who received CBT-I, representing a clinically relevant eight point reduction. Effects were durable up to 6 mo. The quality of the evidence supports a strong recommendation for the use of CBT-I among cancer survivors.